Edukasi Bahaya Pergaulan Bebas Pada Remaja di SMA Kristen Kota Palangka Raya - Yana Afrina; Dinda Anindita Salsabilla (Compromise Journal Community Proffesional Service Journal, 2024)
Adolescence is marked by a period of searching for a suitable lifestyle and often using trial and error, even though there are many mistakes. Teenagers are the most influential generation in realizing the ideals of a country or nation, the nation's next generation, and are expected to be able to bring change to their country to become a better country. In Indonesia, the current condition of teenagers is very worrying, there are many facts that are happening at the moment, young people and young people are falling into the valley of adultery (free sex), this is due to too much freedom in socializing. The main cause of this problem is a lack of public understanding. regarding the boundaries of social relations between men and women. Promiscuity will have a negative impact on the growth and development of children and adolescents. Based on the results of health education regarding the dangers of promiscuity in Christian high school teenagers, it shows that students who take part in the education can follow the presentation of the material until the end, then can also answer questions well during the question and answer session.